(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated principals’ teamwork practices as predictors of teachers’ job performance in secondary schools in Ebonyi State. Two research questions with corresponding two research hypotheses guided the study. The hypotheses were tested at 0.05 level of significance. The study adopted correlational research design. The population of the study comprised all the 4,146 teachers in the 233 public secondary schools in Ebonyi State. While the sample size for the study was 622 teachers obtained using proportionate stratified sampling technique. A researcher-designed questionnaires were used to collect information from the respondents. The instruments were subjected to face and content validity by three experts. The internal consistency of the instrument was determined using Cronbach’s Apha reliability. The co-efficients of 0.80 and 0.78 were obtained respectively. The average index was 0.79, showing that the instruments are reliable. Simple regression and multiple regression were used to answer research questions and test the hypotheses. Major findings which included among others was that principals’ participatory decision making process significantly predicted teachers’ job performance in secondary schools. The study also found that principals’ use of committee system significantly predicted teachers’ job performance in secondary schools in Ebonyi state. It was, therefore, recommended, among others, that principals should offer opportunity for teachers to air their views on instructional matters, which would motivate teachers to improve on their job performance. It was also recommended that principals should not use teachers’ views against them so that they would not withhold their opinions about teamwork challenges.